Analysing AIDA Model Implementation On Instagram: A Case Study Of Smes In The Service Sector In Enhancing Consumer Purchase Decisions - Wahyu Dede Gustiawan; Budi Rahayu; Nindi Vaulia Puspita; Priyo Priyantoro; Priyo Prasetyo (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyse the Instagram content strategy of Defaros Barbershop in Kediri City using the AIDA model (Attention, Interest, Desire, Action) to enhance consumer purchasing decisions. The research background is rooted in the importance of social media optimisation for SMEs in the digital era, where 71% of Indonesian businesses use Instagram, but only 30% utilise it effectively. A qualitative case study design was employed, including content analysis of 60 Instagram posts (January 2022–December 2023), interviews with account managers, and AIDA-based thematic coding. Results revealed that Defaros Barbershop successfully captured attention through aesthetic visuals (78% of posts), retained interest with educational content (40% of posts), and built desire via visual testimonials (30% of posts). However, FOMO-based promotions were only executed 4 times/year, and Instagram Shopping integration was suboptimal. The action stage was supported by clear CTAs (85% of captions) and an average DM response time of 15 minutes. The study concludes by emphasising the need to improve geolocation hashtags, interactive features (polls/Q&A), and promotion frequency to boost conversions. These findings serve as a practical guide for service-orientated SMEs to optimise Instagram with a structured and low-cost approach.